The Combination effect of husk-pulp compost of Durio zibethinus and chicken manure with SP-36 about Chemist characteristic and and growth of maize (Zea mays L.) on Ultisol - fenidea zaneta; fauzi jamal; benny hidayat (Universitas Sumatera Utara, 2018)
The objective of this research is to know the chemist characteristic and growth of maize (Zea mays L.) due to the combination of organic material and SP-36 on Ultisol. This study used randomized block designed which consist of 2 factors and 3 replications. The first factor is organic material: A (0 ton/ha), B (30 ton/ha husk-pulp compost of Durio zibethinus), C (22,5 ton/ha husk-pulp compost of Durio zibethinus + 7,5 ton/ha chicken manure), D (15 ton/ha of husk-pulp compost of Durio zibethinus + 15 ton/ha chicken manure), E (7,5ton/ha husk-pulp compost of Durio zibethinus +22,5 ton/ha chicken manure), F (30 ton/ha chicken manure) and the second factor is SP-36 : P0 (0 kg P2O5/ha), P1 (100 kg P2O5/ha), P2 (200 kg P2O5/ha), P3 (300 kg P2O5/ha). The results showed that the combination of organic materials significantly influenced soil pH, C-Organic, P-available soil, plant height, dry weight and dry root plant. Aplication SP-36 fertilizer significantly increased P- available soil, plant height , dry weight and dry root plant. The interaction of combination of organic matter and SP-36 fertilizer significantly increased P plant uptake. Best dose on this research is 7,5 ton/ha of husk-pulp compost of Durio zibethinus and 22,5 ton/ha chicken manure and 200kg P2O5/ha of SP-36 fertilizer. Keywords: chicken manure, husk-pulp compost of Durio zibethinus, SP-36 fertilizer, Ultisol